2009
DOI: 10.1590/s0100-83582009000200017
|View full text |Cite
|
Sign up to set email alerts
|

Influência da aplicação de glyphosate na queda de frutos e de folhas de coqueiros

Abstract: O objetivo deste trabalho foi avaliar a queda de frutos e de folhas de coqueiros após a aplicação do herbicida glyphosate. O experimento foi instalado no município de Neópolis-SE, no período de agosto a setembro de 2007. O coqueiral da variedade Anão-Verde foi implantado há 11 anos, em área sob sistema de irrigação por microaspersão. O delineamento experimental foi o inteiramente casualizado, com cinco repetições, em esquema fatorial 3 x 3 + 1, sendo três doses do herbicida glyphosate (3,4; 6,8; e 13,6 g por p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Many studies related to the simulation of drifting with subdoses of glyphosate applied in cultures have been reported on the following crops: corn (BROWN et al, 2009;REDDY et al, 2010), eucalyptus (MACHADO et al, 2010;TUFFI SANTOS et al, 2007), cotton (YAMASHITA;GUIMARÃES, 2005GUIMARÃES, , 2006, fruits (GRAVENA et al, 2009;PROCÓPIO et al, 2009;WAGNER JÚNIOR et al, 2008), vegetables (FIGUEREDO et al, 2007;RIGOLI et al, 2008) and physic nuts (COSTA et al, 2009). França et al (2010a) assessed the growth of coffee plants submitted to subdoses of glyphosate, and they reported that plants recover their growth in the aerial part and that the visual symptoms of intoxication decreases after 120 days of application.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies related to the simulation of drifting with subdoses of glyphosate applied in cultures have been reported on the following crops: corn (BROWN et al, 2009;REDDY et al, 2010), eucalyptus (MACHADO et al, 2010;TUFFI SANTOS et al, 2007), cotton (YAMASHITA;GUIMARÃES, 2005GUIMARÃES, , 2006, fruits (GRAVENA et al, 2009;PROCÓPIO et al, 2009;WAGNER JÚNIOR et al, 2008), vegetables (FIGUEREDO et al, 2007;RIGOLI et al, 2008) and physic nuts (COSTA et al, 2009). França et al (2010a) assessed the growth of coffee plants submitted to subdoses of glyphosate, and they reported that plants recover their growth in the aerial part and that the visual symptoms of intoxication decreases after 120 days of application.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos têm evidenciado os efeitos negativos da deriva de glyphosate em: eucalipto (Tuffi Santos et al, 2005), algodoeiro (Yamashita & Guimarães, 2006), soja (Ellis & Griffin, 2002), milho (Magalhães et al, 2001), arroz irrigado (Ferreira et al, 2006), varjão (Parkia multijuga) , citros (Gravena et al, 2009), amendoim (Lassiter et al, 2007), tomate (Figueredo et al, 2007;Santos et al, 2007), coqueiro (Procópio et al, 2009) e pêssego (Tuffi Santos et al, 2006). Nesses trabalhos foram constatadas mudanças morfológicas e anatô-micas nas folhas, causando diminuição na absorção de nutrientes e favorecendo a incidência de doenças, além de, em muitos casos, provocar menor crescimento e produtividade das culturas.…”
Section: Introductionunclassified